PREDIKTOR PERILAKU PEMILIH PADA PEMILUKADA: Perspektif Psikologi Politik - Daud, Muhammad (Jurnal Psikologi TALENTA, 2015)
Local election democracy has been instrumental in increasing the political partaicipation of society, to obtain local leaders who are elected democratically. Local election as mechanisms of local democracy in Indonesia, have an impact on voter behavior tendencies. This study aims to discuss the essence of the local election in the dynamics of local politics and democracy as well as its relationship with the trend of voter behavior. Based on the various theories and research, found that voting behavior is influenced by many factors, including sociological factors, psychological factors, economic factors and factors of mass media. These factors apparently also found in the implementation of the General Election in Indonesia and partaicularly in South Sulawesi.